Association among epicardial fat, heart rate recovery and circadian blood pressure variability in patients with hypertension. Issue 1 (December 2015) - Kim, Da-Jung; Cho, Kyoung-Im; Cho, Eun-A; Lee, Jin-Wook; Park, Hyun-Joon; Kim, Sun-Min; Kim, Hyun-Su; Heo, Jung
Abstract Background Epicardial fat tissue is known to have an unique endocrine function which affect the cardiac autonomic system. Heart rate recovery (HRR) is a simple non-invasive measurement that assesses autonomic nervous system dysfunction. We aimed to investigate the association among epicardial fat thickness (EFT), HRR and circadian blood pressure (BP) variation in patients with hypertension. Methods A total of 358 consecutive patients who underwent both 24-hour ambulatory BP monitoring (ABPM) and a treadmill test were enrolled. Echocardiographic EFT and HRR, defined as peak heart rate minus heart rate after a 1-min recovery time, were measured. Patients were classified according to the ABPM; 147 patients with hypertension with a dipping pattern at night (dippers), 140 patients with hypertension with a non-dipping pattern at night (non-dippers) and 71 normotensive controls. Results EFT was significantly higher in hypertensive patients, especially in the non-dipper group, compared to the controls (non-dippers, 7.5 ± 2.9 mm; dippers, 6.6 ± 1.6 mm; controls, 5.5 ± 2.1 mm;p < 0.001). HRR was significantly lower in both hypertensive groups as compared to the control group and was the lowest in the non-dipper group (non-dipper, 26.6 ± 18.6; dipper, 29.5 ± 21.5; control, 71.4 ± 19.8;p < 0.001). EFT was significantly correlated with age, body mass index, 24-hour mean systolic BP and 24 h mean BP variability, whereas exercise duration, metabolic equivalents (METs) and HRR were inversely correlated with EFT. Furthermore, EFT > 6.7 mm was associated with a blunted HRR with 76 % sensitivity and 61 % specificity (ROC area under curve: 0.71, 95 % confidence interval, CI = 0.65–0.76, p < 0.001). In a multivariate analysis, EFT (odds ratio, OR = 3.53, 95 % CI = 1.20–10.37, p = 0.022) and 24-hour mean BP variability (OR = 1.09, 95 % CI = 1.03–1.16, p = 0.005) were independent predictors of a blunted HRR defined as HRR ≤ 12 beats (n = 63) in patients with hypertension. Conclusion EFT and HRR were significantly correlated with circadian BP variability in patients with hypertension. EFT and circadian BP variability were independent predictors of blunted HRR, which suggests a link between epicardial fat and autonomic dysregulation in hypertension.